A multi-objective mathematical model to redesign of global sustainable bioenergy supply network. (2nd September 2019) - Razm, Sobhan; Nickel, Stefan; Sahebi, Hadi
Highlights: Developing a multi-objective optimization model to redesign of GSBE-SNR considering incoterms. Integrating social objectives into multi-objective model. Greenhouse gas emission savings are maximized in the global sustainable bioenergy network. Using GIS software to draw precise maps of the studied countries before and after redesigning. Iran-o-Armenia case study with taking the sustainability conditions of each country into account. Abstract: In today's industrial world, depletion of fossil resources and the adverse environmental effects of consuming fossil fuels have become one of the serious challenges in sustainable development of the societies. In recent years, substantial attention has been paid to using biomass for producing bioenergy in order to increase economic performance, reduce environmental effects, and providing new opportunities in different societies in pursuit of sustainable development. The complexities related to procurement, logistics, technology selection, raw material management (biomass), and product distribution planning are the main causes of using the optimization models to design the bioenergy supply chains. On the other hand, the globalization of economy and industry increased the significance of the subjects related to global logistics and the ecological and social objectives of the countries have undeniable influences on each other. Hence, in this paper, a mathematical model has been developed to redesign a global bioenergy supply network. This model has simultaneously studied the economic, environmental, and social objectives and the environmental coefficients of the model were calculated using SimaPro software. The multi-objective model was solved by augmented ɛ-constraint method and the decision makers were informed of the obtained Pareto solutions. Data taken from the study on Iran and Armenia was used to validate the model and the Geographic information system (GIS) software was used with the goal of studying the geographical map of each country more accurately.